Konsep Harta dan Pengelolaannya dalam Al-Qur'an - Toha Andiko (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2016)
Understanding wealth (al-mal) in the Qur’an includes food (tha`am), soil (ardhun), and money (dirham). Meaning of senonim with al-mal is qintharah, tsamarun, kanzun, khaza’in, maghanim, al-anfal, mata`, al-khair, and al-turath. According to the Koran, Alloh is the absolute owner of wealth. Wealth as private asset is intended for direct human character and attitude to look for, own, and use it on the right path. Wealth as belonging together meant that all humans have the opportunity to look for wealth, no one is given the right to strict circulation of wealth in the human environment and in every one’s wealth there are parts of others. Function of wealth as a provision for worship, support life, as a test of faith, the support to be a leader, and one of the jewelry of life. Obtaining wealth should not be by way of vanity, its use must be balanced, the management must be careful, honest, sincere, and transparent and able to provide benefits to the community.